An Empirical Study of Blended Teaching Mode Based on SPOC in the Postpandemic Era - Xiaoning Chen; Jin Guo; Hongyan Xu (Discrete Dynamics in Nature and Society)
The COVID-19 pandemic broke the normal of school education and sounded the horn for future education reform. This paper designs the online and offline mixed teaching mode of the SPOC platform in the postpandemic era according to the actual situation of teaching at application-oriented colleges and universities, and the blended teaching mode is applied to real teaching scenarios. The teaching effect and students’ behaviors are analyzed in such scenarios. Empirical research shows that the situational teaching model based on mixed SPOC for course design, teaching resources are more abundant, and task assessments are more reasonable. Through the questionnaire survey, about 95% of the students think that the learning mode based on SPOC has improved their learning interest, autonomous learning ability, and problem-solving ability, which is much higher than the assessment of traditional courses. The exploratory practice has shown that the online and offline blended teaching mode based on SPOC can dramatically improve teaching quality.